2018
DOI: 10.1002/psp.2195
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational and interethnic mental health: An analysis for the United Kingdom

Abstract: This paper uses a nationally representative data set to examine the extent to which family migration history helps explains interethnic variations in mental health in the United Kingdom. We confirm that there is significant variation in mental health across ethnic group and generation of migration. Furthermore, we show how these dimensions interact. The analysis explores the extent to which neighbourhood, personal characteristics, and migration experience are related to mental health. We find evidence that all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…Living in areas of high ethnic density is also expected to lower exposure to ERH due to lesser likelihood of contact with majority group members (Halpern and Nazroo 1999;Becares, Nazroo, and Stafford 2009;Dustmann, Fabbri, and Preston 2011), and to "buffer" its impact on health when it does occur (Becares, Nazroo, and Stafford 2009;Karlsen and Nazroo 2002;Pickett and Wilkinson 2008). There is also evidence of considerable heterogeneity in the ethnic density effect, both by the characteristics of the neighbourhoods themselves (Becares et al 2012) and between the UK and foreign born (Dorsett, Rienzo, and Weale 2019;Schofield et al 2017).…”
Section: Ethnic Attachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Living in areas of high ethnic density is also expected to lower exposure to ERH due to lesser likelihood of contact with majority group members (Halpern and Nazroo 1999;Becares, Nazroo, and Stafford 2009;Dustmann, Fabbri, and Preston 2011), and to "buffer" its impact on health when it does occur (Becares, Nazroo, and Stafford 2009;Karlsen and Nazroo 2002;Pickett and Wilkinson 2008). There is also evidence of considerable heterogeneity in the ethnic density effect, both by the characteristics of the neighbourhoods themselves (Becares et al 2012) and between the UK and foreign born (Dorsett, Rienzo, and Weale 2019;Schofield et al 2017).…”
Section: Ethnic Attachmentmentioning
confidence: 99%
“…A final contribution of this paper is to differentiate between foreign born (first generation) and UK born ethnic minorities (second+ generation) when examining the relationship between ERH, mental health and ethnic attachment (Dorsett, Rienzo, and Weale 2019;Nandi, Luthra, and Benzeval 2016). We expect higher reports of ERH and a more detrimental mental health impact of ERH for the latter group for a number of reasons.…”
Section: Generation Status Harassment and Healthmentioning
confidence: 99%
“…The healthy migrant effect and the further loss of this effect after one generation have been suggested as a potential explanation . Evidence also suggests that being able to maintain cultural links or live in areas with higher proportion of people from the same ethnic group may outweigh other hurdles and contribute to better well‐being in general or pregnancy outcomes in particular in ethnic minority groups . Unfortunately, we were unable to further explore these factors because of a lack of relevant data in our dataset.…”
Section: Commentmentioning
confidence: 99%
“…Additionally, mental health status differs according to ethnicity [37]. Dutch studies have identified ethnic origin as an individual predictive factor for common mental disorders, showing an increased risk of affective disorders among Moroccan and Turkish immigrants [38], and higher odds of anxiety, depression and PTSD for Iranian immigrants compared with those from Somalia and Afghanistan [39].…”
Section: Introductionmentioning
confidence: 99%